Application of microfacies analysis in the Lower Devonian of the Barrandian, central Bohemia - Velebilova,L.; Sarf,P. (Journal of the Czech Geological Society, 1996)
Microfacies analysis using the Standard Microfacies (SMF) Types (Wilson 1975, Flugel 1982) was made on the Lower Devonian (Lochkovian, Pragian, Zlichovian) carbonates in the two localities in the Barrandian area: the Radotin Valley and the Cerinka quarry. The research resulted into the definition of 8 microfacies types, not fully corresponding to the SMF Types: A - packstone with abundant bioclasts, B - biomicrite, C - microbioclastic calcisiltite, D - packstone with calcisiltite matrix, E - coarse bioclastic limestone or lithoclastic breccia, H - nonfossiliferous micrite, 1 - laminite with peloids, J - spiculite. The microfacies criteria are used for determining the sedimentary environment and its development through the Lower Devonian is reconstructed.
Keywords: Devonian; limestones; sedimentology; microfacies; Barrandian area; Bohemia